The Relationship Between Social Support with Entrepreneurial Intentions for Beauty Training Graduates at BPVP Padang City - Putri, Rahmawati; Solfema, Solfema (Universitas Negeri Padang, 2024)
This research was motivated by the low entrepreneurial intentions of beauty training graduates at BPVP Padang City. This is because of the low level of social support received by beauty training graduates. This research aims to see a picture of social support, a picture of entrepreneurial intentions, and determine the relationship between social support and entrepreneurial intentions for beauty training graduates.This type of research is quantitative research with a correlational type. The population in this study were beauty training graduates with a total population of 64 beauty training graduates and the sample in this study was 48 beauty training graduates. The sampling technique uses Stratified Random Sampling. Data collection techniques using questionnaires are distributed via g-form. For data analysis techniques, use the percentage formula and product moment correlation formula.The results of this research show that: (1) Social support is categorized as low, (2) Entrepreneurial intentions are categorized as low, (3) There is a significant relationship between social support and entrepreneurial intentions for Padang City BPVP beauty training graduates. Recommended to: (1) BPVP Padang City can provide support and assistance in entrepreneurship. (2) To Educators or Instructors to further increase social support and entrepreneurial intentions which are not yet high. (3) To other researchers so they can look for other variables that can influence entrepreneurial intentions.Keywords: Social Support, Entrepreneurial Intentions.